Studi Mikrotremor untuk Zonasi Bahaya Gempabumi Daerah Surakarta Provinsi Jawa Tengah - , MUHAMMAD ADITIA DWI IRFANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Earthquake is one of the most frequent natural disasters in Indonesia. Java, especially Central Java province including Surakarta area is an area that is prone to earthquakes. Earthquakes as a source of natural disasters that can be explained on the sources and mechanisms, but so far have not predictable as to when, where and how big the disaster happened exactly. The need to know the characteristics of the land in response to a wave of earthquakes in order to estimate the extent of the vulnerabilities in Surakarta. Given the Yogyakarta earthquake in 2006 there were similarities types of lithology or sediment constituent in Klaten area ( the area affected by a severe impact ) with the Surakarta area where most of the region is composed of sediments that quarter should also know how much the level of vulnerability to earthquake hazards in Surakarta. Another factor that has Surakarta population density highest in Central Java Province. The tools used in measuring mikrotremor wave is 1.0 Hz seismometer 3 components ( L4 - 3C ) in which the measurement mechanism utilizes natural wave as a noise or vibration source so no need to wait for an earthquake to obtain the data. HVSR method , or more commonly called the Nakamura method , is an empirical technique to estimate the resonance characteristics of the sediment layers below the surface. This method uses the measurement data mikrotremor wave or natural noise amplification and to determine the value of the dominant frequency of the field. The results of the analysis are presented in graphical form HVSR analysis. In this study mikrotremor measurements performed at 90 points evenly distributed in five districts of Surakarta, Central Java Province with the distance between the location of the measurement Â± 1 km and the measurement of the time duration of each location for 10 minutes. Based on the measurement data mikrotremor with HVSR analysis is then possible earthquake hazard zoning based on a number of parameters that is the amplification, the frequency, the dominant period, sediment thickness, seismic vulnerability index, distance to active faults and the Peak Ground Acceleration (PGA) in Surakarta area. Based on the overlay to the map then produces five types of earthquake hazard zonation map of the area in Surakarta, Central Java Province is divided into 2 zones of earthquake hazard that is Medium Vulnerability Zone and Higher Vulnerability Zone.